Rosuvastatin induced gynecomastia: a rare presentation of newer statin - Ruhela, Suman; Ruhela, Manish; Ola, Rakesh Kumar; Rao, Mahesh (International Journal of Basic & Clinical Pharmacology, 2020)
Gynecomastia is a common benign disease characterized by the progressive enlargement of the glandular tissue of the male breast. The etiology may vary and may be physiological, pharmacological, pathological, or even idiopathic. Among men, drug induced gynecomastia may account for 10-20% of cases. Several case reports have associated this condition to the use of statins. However, there are few case reports of rosuvastatin induced gynecomastia have been reported in literature. We describe a 45-year-old male who developed bilateral gynecomastia after one month of rosuvastatin therapy, after switching to a different or less potent statin (atorvastatin), his symptoms resolved with-in one month. Use of the Naranjo adverse drug reaction probability scale indicated a possible relationship between the patient’s development of gynecomastia and rosuvastatin therapy.